2009
DOI: 10.1056/nejmoa0901075
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence of Bile Salt Export Pump Deficiency after Liver Transplantation

Abstract: Severe bile salt export pump (BSEP) deficiency is a hereditary cholestatic condition that starts in infancy and leads to end-stage liver disease. Three children who underwent orthotopic liver transplantation for severe BSEP deficiency had post-transplantation episodes of cholestatic dysfunction that mimicked the original disease. Remission of all episodes was achieved by intensifying the immunosuppressive regimen. The phenotypic recurrence of the disease correlated with the presence of circulating high-titer a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
92
1
5

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(102 citation statements)
references
References 19 publications
4
92
1
5
Order By: Relevance
“…Jara et al reported recurrence of cholestasis and pruritus following LT in BSEP patients with no evidence of cellular rejection on liver biopsy in 2009 [36]. In the same year, BSEP antibodies in the serum and at the hepatocyte canalicular membrane of a single patient who underwent two liver transplants were described [37].…”
Section: Bsep Deficiencymentioning
confidence: 99%
“…Jara et al reported recurrence of cholestasis and pruritus following LT in BSEP patients with no evidence of cellular rejection on liver biopsy in 2009 [36]. In the same year, BSEP antibodies in the serum and at the hepatocyte canalicular membrane of a single patient who underwent two liver transplants were described [37].…”
Section: Bsep Deficiencymentioning
confidence: 99%
“…Aggressive plasma cellrich interface or perivenular necro-inflammatory activity or inflammatory bile duct damage has not been described [230][231][232].…”
Section: Metabolic Diseases and Toxic Insultsmentioning
confidence: 99%
“…Patients in the first group who failed medical or other surgical therapy, if available, are prime candidates for liver transplantation because the cirrhotic liver is replaced by a genetically and structurally normal one that generally cures the disease. Some familial intrahepatic cholestasis syndromes, however, recur after transplantation because of de novo antibodies that develop in response to mutated non-inherited proteins that are introduced with the donor organ (see AIH section) [230][231][232].…”
Section: Histopathology and Differential Diagnosismentioning
confidence: 99%
“…7 After liver transplantation a recurrence of PFIC in the allograft because of allo-immunisation of the recipient against BSEP protein of the donor has been reported. 19,20 Management (please describe)…”
Section: Prognosis (Please Describe)mentioning
confidence: 99%